Comparison of Endometrial Microbiota Results Between Patients with Unexplained Infertility and Fertile Patients through 16s rRNA Sequencing - Ozten Dere, Gonca; Tan, Cagman; Mumusoglu, Sezcan; Zarakolu, Pinar; Bozdag, Gurkan (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: The primary objective of our study was to compare the endometrial microbiota profiles of women with unexplained infertility and fertile women. STUDY DESIGN: In this case control study a total of 15 patients with unexplained infertility and 15 patients who had a live birth in the last two years with proven fertility were recruited. Endometrial samples were collected and analyzed through next-generation sequencing of the bacteria-specific 16S ribosome gene. RESULTS: Lactobacillus species represented the majority of the microbiome profile in both groups. The median percentage of the endometrial Lactobacillus between infertile patients and fertile patients was not statistically significant (p=0.9). Groups were divided into two categories: Lactobasillus dominant (Lactobacillus spp.> 90%, LD) and Non-Lactobacillus dominant (NLD). Lactobacillus dominance was detected in six of nine patients (66.7%) in the study group and four of nine patients (44.5%) in the control group, and no significant difference was observed between them (p=0.64). CONCLUSION: According to our study results, no significant difference was observed between the endometrial microbiota profile of infertile and fertile patients. Further studies with larger sample sizes are needed to characterize the endometrial microbiota and its impact on reproduction. Keywords: Microbiota, unexplained infertility, endometrial microbiota